Effects of Hyperoxia on Aging Biomarkers: A Systematic Review - Tessema, Belay; Sack, Ulrich; Serebrovska, Zoya; König, Brigitte; Egorov, Egor (Frontiers in Aging, 2022)
The effects of short-term hyperoxia on age-related diseases and aging biomarkers have been reported in animal and human experiments using different protocols; however, the findings of the studies remain conflicting. In this systematic review, we summarized the existing reports in the effects of short-term hyperoxia on age-related diseases, hypoxia-inducible factor 1α (HIF-1α), and other oxygen-sensitive transcription factors relevant to aging, telomere length, cellular senescence, and its side effects. This review was done as described in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. A systematic search was done in PubMed, Google Scholar, and Cochrane Library and from the references of selected articles to identify relevant studies until May 2021. Of the total 1,699 identified studies, 17 were included in this review. Most of the studies have shown significant effects of short-term hyperoxia on age-related diseases and aging biomarkers. The findings of the studies suggest the potential benefits of short-term hyperoxia in several clinical applications such as for patients undergoing stressful operations, restoration of cognitive function, and the treatment of severe traumatic brain injury. Short-term hyperoxia has significant effects in upregulation or downregulation of transcription factors relevant to aging such as HIF-1α, nuclear factor kappa-light-chain-enhancer of activated B-cells (NF-kB), and nuclear factor (erythroid-derived 2)-like 2 (NRF2) among others. Short-term hyperoxia also has significant effects to increase antioxidant enzymes, and increase telomere length and clearance of senescent cells. Some of the studies have also reported adverse consequences including mitochondrial DNA damage and nuclear cataract formation depending on the dose and duration of oxygen exposure. In conclusion, short-term hyperoxia could be a feasible treatment option to treat age-related disease and to slow aging because of its ability to increase antioxidant enzymes, significantly increase telomere length and clearance of senescent cells, and improve cognitive function, among others. The reported side effects of hyperoxia vary depending on the dose and duration of exposure. Therefore, it seems that additional studies for better understanding the beneficial effects of short-term hyperoxia and for minimizing side effects are necessary for optimal clinical application.